RECONSTRUCTION OF PENAL MEDIATION AS ALTERNATIVE COMPLETION CRIMINAL CRIMINAL ACTIONS BY THE INCIDENTAL BASED EDUCATION VALUE OF UTILIZATION - song sip (Jurnal Pembaharuan Hukum, 2017)
AbstractThe settlement of cases in a criminal case is an option of dispute resolution involving a third party. The mediation of the penal is not only justified, as it not only exists, and is used and proves in sociological justification. The existence of penal mediation as a legal means of settling criminal cases, especially the settlement of alleged criminal act of fraud is justified in the legislation, that is Law no. 2 Year 2002 with the concept of discretion. The theory of dignified justice shows the pancasila value derivation, volksgeist Indonesian nation. Based on the Four Precepts is a philosophical deliberation of consensus, led by the wisdom. The reconstruction of the concept of authoritative discretionary powers mediates the penalty of fraud criminal cases, and is within the jurisdiction of the investigator or at the level of investigation of the value of justice with dignity based on justice.